2011
DOI: 10.1186/1472-6963-11-7
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual models for Mental Distress among HIV-infected and uninfected individuals: A contribution to clinical practice and research in primary-health-care centers in Zambia

Abstract: BackgroundMental distress is common in primary care and overrepresented among Human Immunodeficiency virus (HIV)-infected individuals, but access to effective treatment is limited, particularly in developing countries. Explanatory models (EM) are contextualised explanations of illnesses and treatments framed within a given society and are important in understanding an individual's perspective on the illness. Although individual variations are important in determining help-seeking and treatment behaviour patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Despite a global prevalence of 13%, inclusive of neurological and substance use disorders, mental disorders do not attract much attention [4]. The magnitude of mental disorders is amplified when comorbid with other disorders such as HIV/AIDS and coronary heart disease [5,6]. Projections for this disease burden were set to increase to about 15 per cent by 2020 and depression producing the second most significant disease burden across all age groups.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a global prevalence of 13%, inclusive of neurological and substance use disorders, mental disorders do not attract much attention [4]. The magnitude of mental disorders is amplified when comorbid with other disorders such as HIV/AIDS and coronary heart disease [5,6]. Projections for this disease burden were set to increase to about 15 per cent by 2020 and depression producing the second most significant disease burden across all age groups.…”
Section: Introductionmentioning
confidence: 99%
“…Many newly diagnosed PLWHA suffer from psychological stress like depression, anxiety, hopelessness, and suicidal ideation [811]. Perceived stresses also often present as physical symptoms such as headaches, sleep disturbances, fatigue, loss of appetite, and sexual difficulties [12]. …”
Section: Introductionmentioning
confidence: 99%
“…For example, Patel, Gwanzura, and Simunyu (1995) explored the ways in which primary health care patients in Zimbabwe account for their emotional distress, highlighting patients' emphasis on spiritual factors, particularly the stresses of being bewitched by others, as the most common explanation for distress. In Zambia, Chipimo, Tuba, and Fylkesnes (2011) and Aidoo and Harpham (2001) found that patients explained mental distress as a social and cultural experience rather than a medical one, defining it as "problems of the mind", and pinpointing social relationships, poverty and unemployment as primary causal factors. Interestingly the exception here was patients with AIDS, who, despite giving similar accounts of the social drivers of distress, tended to draw on more medical terminology in listing the symptoms of their distress, probably due to their greater familiarity with western health service settings.…”
mentioning
confidence: 99%